REMOTE MEASUREMENT OF FLOW RATES OF POLLUTED WATER WITH DOPPLER VELOCIMETRY - Gondal, M. A. (2020)
A Doppler Velocimeter for monitoring the flow rates of liquid and gaseous pollutant discharges remotely has been developed. The system has been tested for the measurement of polluted water and gaseous discharges. It is calibrated with a rotating wheel at constant speed. The system has also been used to study gaseous discharges and to investigate turbulent flow profiles of water. The system is capable of measuring Doppler shifts as low as 0.25 MHz corresponding to 0.1 m/sec velocities of the fluids.